Dose–response relationship of serum ferritin and dietary iron intake with metabolic syndrome and non-alcoholic fatty liver disease incidence: a systematic review and meta-analysis - Yu, Lu; Que, Ting; Zhou, Yifeng; Liu, Zhengtao (Frontiers in Nutrition, 2024)
Aim: This study aims to assess the dose-response impact of iron load on systemic and hepatic metabolic disorders including metabolic syndrome (MetS) and nonalcoholic fatty liver disease (NAFLD). Methods: Serum ferritin (SF) and dietary iron intake were selected to represent the indicators of iron load in the general population. PubMed, EMBASE and Web of Science databases were searched for epidemiological studies assessing the impact of SF/dietary iron intake on MetS/NAFLD occurrence. All literature was published before September 1 st ，2023 with no language restrictions. Results: Fifteen and eleven papers were collected with a focus on connections between SF and MetS/NAFLD, respectively. Eight papers focusing on dietary iron and MetS were included in the following meta-analysis. For the impact of SF on MetS, the pooled odds ratio (OR) of MetS was 1.88 (95% CI: 1.58-2.24) for the highest versus lowest SF categories. In males, the OR was 1.15 (95% CI: 1.10-1.21) per incremental increase in SF of 50 μg/L, while for females, each 50 μg/L increase in SF was associated with a 1.50-fold higher risk of MetS (95% CI: 1.15-1.94). For connections between SF and NAFLD, we found higher SF levels were observed in NAFLD patients compared to the control group(standardized mean difference [SMD] 0.71; 95% CI: 0.27-1.15), NASH patients against control group (SMD1.05;95%CI:0.44-1.66), NASH patients against the NAFLD group (SMD0.6;95%CI:0.31-1.00), each 50 μg/L increase in SF was associated with a 1.08-fold higher risk of NAFLD (95% CI: 1.07 -1.10).For the impact of dietary iron on MetS, Pooled OR of MetS was 1.34 (95%CI: 1.10-1.63) for the highest versus lowest dietary iron categories. Conclusion: Elevated SF levels is a linear relation between the incidence of MetS/NAFLD. In addition, there is a positive association between dietary iron intake and metabolic syndrome. The association between serum ferritin and metabolic syndrome may be confounded by body mass index and C-reactive protein levels.